Implementação de Lean Construction e BIM como parte de objetivos estratégicos de empresas de construção: um estudo de caso do setor da construção civil - Landim, Gabriela Linhares (2023)
Several studies have been carried out on the synergy between Lean Construction and BIM, but most of them have been focused on the application of tools, with an operational focus and specific stages of the project's life cycle. However, some researchers have already warned that the integration of Lean Construction and BIM, in line with the strategic objectives of companies, can result in a higher gain in productivity and reduction of waste. There are few studies that seek to investigate the long-term implementation of Lean Construction and BIM in construction companies in order to take full advantage of the existing synergy. Thus, the present work aims to evaluate the integration process between BIM and Lean Construction in construction companies from a strategic perspective. In view of this, the present work is characterized as an exploratory and descriptive study with a qualitative approach. The research strategy adopted was the Case Study, organized in three phases. The first phase involved the foundation and understanding of the research topic and was composed of the Systematic Literature Review (SLR), in which knowledge was sought about strategic implementations of Lean Construction and BIM separately and together. This knowledge was used to prepare an interview script. The second phase consisted of conducting semi-structured interviews with representatives of companies that already have Lean and BIM implemented, in order to learn about the processes the companies went through to achieve implementation, in addition to the difficulties and contributions of each implementation. And the third phase consisted of analyzing the content of the interviews to draw generalizable conclusions about good practices for implementing Lean and BIM and their integration and description of the theoretical and practical contributions of the case studied.